PELAYANAN TERHADAP PENGGUNA ANGKUTAN DAMRI TRAYEK BEKASI BARAT-BANDARA SOEKARNO HATTA - Payaman Manik; Marcelina Sitorus; Endang Sugiharti (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of the research is to find out how big the effect of service to the passengers of DAMRI route west Bekasi – Soekarno Hatta airport. The types of services regulated in SK.97 / HK.003 / DAMRI-2012 on Minimum Service Standards (SPM) Integrated Transportation Mode determine the quality of transport services that will affect the user decisions on DAMRI route West Bekasi - Soekarno Hatta Airport in 2016. This study was analyzed by descriptive statistics and inferential statistics with questionnaires spread of 100 respondents. The result of analysis shows that there is a significant influence simultaneously between the variables of service quality to user/passengers decision on DAMRI route west Bekasi – Soekarno Hatta airport. Partial analysis results show that security, safety, convenience, affordability, and equality variables do not have a significant effect on user/passengers decision. However, order has a significant effect on user/passengers decisions.